Spesifikasi dan Konstruksi Pancing Cumi di Muara Baru Jakarta Utara - Rasdam Rasdam; Mokhamad G. Bagaskara (Jurnal Airaha, 2020)
The purpose of this study was to determine the type, specifications and construction of the Squid hand fishing line. The method used is descriptive method that is to make a description, description, or painting in a systematic, factual and accurate manner about the facts, the characteristics and the relationship between the phenomena investigated. The results of the study found that the specifications and construction of each type of Calamari hand fishing rod were in principle almost the same, but there were differences in the number of lures, bait types, branch line components, main line length and weights. Overall, the main components of Calamara hand fishing construction consist of fishing rods, main lines, branch lines, artificial hooks, swivels, snap and ballast.